Primary health care in health care for homeless people - Laura, Chen; Cruz, Alline Dias; Salles, Marcelo Medeiros; Perillo, Rosângela Durso; Torres, Lilian Machado; Almeida, Shirley Pereira (Journal of Health Care, 2021)
Introduction: the street situation phenomenon is a challenge for its understanding, dimensioning, various diagnoses and for the definition of strategies to face the conditions of vulnerability, including health conditions. Objective: to describe the actions developed by health professionals and the difficulties experienced in the care of the homeless population. Methods: qualitative research, based on interviews with health professionals of a Basic Health Unit in Belo Horizonte-MG, a reference for the care for this population. The content of the statements was analyzed by Bardin’s reference. Results: the professionals identify actions performed, based on the systematized welcoming with a view to creating bonds and addressing the main health problems. They carry out necessary preventive actions and route or trigger other services, such as hostels or pop centers. They feel satisfied and gratified, despite noticing the need for greater articulation with other points of the care network in the face of more complex or specific care. They also face difficulties in reducing harm in various dimensions such as vaccination, oral and general health, mental health and prevention and treatment of chronic and infectious diseases. Two categories emerged: Identifying actions developed by primary care professionals and facing difficulties and challenges in serving this population. Conclusions: it is necessary to overcome prejudices and know the street situation for its implication in the care provided in Primary Care, despite the difficulties. Training professionals and multi- and interdisciplinary planning, in a network, contribute to the quality in the capture of individuals and their effective insertion in health services.